Influence Of Modernity Versus Continuity Of Architectural Identity On House Facade In Erbil City, Iraq - Al-Shwani, Salahaddin Yasin Baper (2011)
This thesis discusses one of the most distinctive issues of architecture debates about modernity and architectural identity. It aims to measure the influence of modernity to architectural identity on house facade in Erbil City, Iraq. The objectives of this research attempt to evaluate the factors' degree of change, develop a model for visual analysis, examine the variations in the perceptions of the respondents and investigate the correlation between house facade modernity factors and its continuity of architectural identity. Through the literature review, the study investigates a conceptual model for modernity and formulates the properties of architectural identity.